The bag of bones - French, Vivian (French, Vivian. Tale from the five kingdoms, 2009)
Grace, alerted to the fact that there is trouble in the Five Kingdoms, joins with her odd assortment of friends in an effort to foil the evil plans of Truda Hangnail, a green-tongued witch who has shrunk all the good witches of Wadington to the size of rats.